The Great Democracies; A History of the English-Speaking Peoples (Vol. 4) - Churchill, Winston S. (New York Bantam Books, 1980)
A History of the English Speaking Peoples.
Include Maps and Index.
Keywords: Great Britain -- English-speaking countries -- Commonwealth countries